Seafloor and Shallow Subsurface of the St. Lawrence River Estuary - Pinet, Nicolas; Brake, Virginia; Campbell, Calvin; Duchesne, Mathieu (Geoscience Canada, 2011)
SUMMARY A new surficial geology map of the St. Lawrence River Estuary illustrates sediment distribution and variability in a relatively confined environment. This map is based on recently collected geophysical and geological data that provide a link between submarine land-forms and sedimentary units. The strong dichotomy between the areas to the northeast and to the southwest of the Saguenay River is the main characteristic of the St. Lawrence River Estuary. To the northeast, the Lower St. Lawrence Estuary is mainly floored by fine silts within the Laurentian Channel and sediments varying from sands to fine silts on its margins. To the southwest, the Middle Estuary corresponds to a high-energy sedimentary environment that precludes the deposition of fine-grained sediments. In the latter area, Holocene sediments are either absent or correspond to a sand unit shaped by currents.